The lever of riches : technological creativity and economic progress - Mokyr, Joel, 1946- (Oxford University Press, 1990)
Why are some nations more technically creative than others and why do some highly innovative societies eventually stagnate? In this provocative study of the value and meaning of technological advance, Joel Mokyr considers how past physical and social conditions have influenced the development and reception of new ideas, and shows how these trends can guide future industrial strategies at a time when more countries than ever before are competing for the rewards of technical ingenuity.